Pantoea Species Bacteremia in a Child With Sickle Cell Disease: Looking for a Culprit. Issue 6 (August 2017) - Oliveira, Marisa I.; Batalha, Sara; Gouveia, Catarina; Maia, Raquel; Kjöllerstrom, Paula
Abstract : Pantoea agglomerans has been classically associated with cellulitis or synovitis secondary to penetrating trauma by vegetation. It is an infrequent cause of systemic infections. We describe the case of a 5-year-old girl with sickle cell disease with P. agglomerans bacteremia and review its potential causes.